IMPROVING STUDENTS SPEAKING SKILL BY USING INTERACTIVE MAPS AT SEVENTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Etika Ariyani (JOEL: Journal of Educational and Language Research, 2023)
This Classroom Action Research (CAR) aims to know the effectiveness of interactive maps as a learning strategy to improve students speaking skills and change speaking classroom situation at seventh grade of Junior High School. Population in this research were 28 seventh grade students from Junior High school in Mataram City – West Nusa Tenggara Province. This research was conducted in two cycles, each cycle consisted of four stages namely planning, acting, observing and reflecting. Procedure of data collection by observing, interview and assessing students speaking skills through post-test. The data were analysed using interactive method and the quantitative data were analysed using descriptive statistic procedure. The result of this research indicated there is improvement from pre-test score to post-test, the score of post – test showed that there were 22 students ( 78.57%) reached higher score than minimum criterion. Only 6 students (28.42%) reached lower score. The implementation of interactive maps improved students speaking skills and change classroom situation significantly. It found that the changes of students speaking skills are influenced by six factors such as interesting learning media, fun English atmosphere, enjoyable classroom, attractive teacher approach, appropriate teacher learning strategy and interesting learning experiences